HVDC Application for Different Solar PV Technology Combinations in India - Suprava Chakraborty; Pradip Kumar Sadhu; Nitai Pal (Institute of Advanced Engineering and Science, 2014)
Conventionally Grid Connected Solar PV plants initially generate DC power and then converted to AC via inverters and connected into AC grid for transmission power. Depending on the size of the plant, required environmental condition and land availability large PV plants are generally located far away from the load centre. Hence reduction of transmission loss and incised transmission capacity expansion is a greater challenge for modern newly establish solar power plant. Transmitting high voltage DC power directly from Solar PV panel to High voltage DC grid is become an accretive option for modern PV power plant. In this paper DC-DC bypass diode converter model is adopted to generate high voltage DC voltage in PV power plant. Result shows that power in the range of HVDC level can be generated when the voltage of different PV technology blocks are used as input. P-SIM software is used for simulating the circuit here.http://dx.doi.org/10.11591/telkomnika.v12i12.6822